KEPERCAYAAN MISTISME KONTEN YOUTUBE (ANALISIS RESEPSI MAHASISWA SURABAYA PADA KONTEN SARA WIJAYANTO) (Universitas Negeri Surabaya, 2023)
Abstract Youtube content as a form of new media has a role as media that describes social reality. The audience as an active audience plays a role as a result of interpreting a media message.The content of Sara's Mystery Diary is a short video with lots of mystical scenes about spirits. The scene will produce different meanings for each individual. With this problem, the research discussed the content of